A new species of Lasjia (Proteaceae) from Sulawesi: Lasjia griseifolia Utteridge & Brambach - Timothy M. A. Utteridge; Liam A. Trethowan; Matilda J. M. Brown; Seth Ratcliffe; Jack Plummer; Fabian Brambach; Himmah Rustiami (Kew Bulletin, 2024)
Summary Lasjia griseifolia Utteridge & Brambach, a member of the Proteaceae, is described and illustrated as a new species from the Indonesian island of Sulawesi. The new species is similar to L. erecta , also from Sulawesi, and morphological differences between the taxa are discussed; a line illustration and detailed notes on the conservation status are provided.